The 4-Octahedra model - Abarca Morales, Edgar (Frontiers in Materials, 2024)
This work comprises a generalization of a simple geometric model originally developed to describe coupled rotations of corner-sharing octahedra in the surface layer of Sr2RuO4 under uniaxial compression. The main objective of the model is to establish a link between the experimental global strain configuration and the possible microscopic mechanisms and compatible geometries by which the octahedra accommodate the applied strain. In achieving this, a useful and intuitive parametrization of four-site two-dimensional systems of corner-sharing octahedra has been established, which can be readily extended to three dimensions and N>4 inequivalent sites or directly employed to analyze the octahedral configuration of many perovskites, transition metal oxides (TMOs), and layered compounds.